2017
DOI: 10.1016/j.jvir.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aspirin Therapy on Ultrasound–Guided Renal Allograft Biopsy Bleeding Complications

Abstract: Purpose To determine if patient aspirin exposure and timing affect bleeding risk after renal allograft biopsy. Materials and Methods Review of 6,700 renal allograft biopsies (in 2,362 unique patients) was performed. Median patient age was 53.0 years [interquartile range 43.0, 62.0]; 56.2% of patients were male. Of biopsies, 4,706 (70.2%) were performed in patients with no aspirin exposure within 10 days of biopsy; 664 (9.9%), were performed within 8–10 days of aspirin exposure; 855 (12.8%), within 4–7 days; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Major complications of allograft biopsy are (a) those that require transfusion, surgical or vascular intervention, unanticipated hospitalization, or transplant removal and (b) death (37). Fortunately, reported rates of these major complications are as low as 0.24% (although reported rates are 0%-4% in the literature) when performed by experienced subspecialist operators, even when supervised trainees are involved (37,41,42).…”
Section: Postbiopsy Renal Avf and Pseudoaneurysmmentioning
confidence: 99%
“…Major complications of allograft biopsy are (a) those that require transfusion, surgical or vascular intervention, unanticipated hospitalization, or transplant removal and (b) death (37). Fortunately, reported rates of these major complications are as low as 0.24% (although reported rates are 0%-4% in the literature) when performed by experienced subspecialist operators, even when supervised trainees are involved (37,41,42).…”
Section: Postbiopsy Renal Avf and Pseudoaneurysmmentioning
confidence: 99%
“…Others have reported chief signs and symptoms of Page kidney including acute pain over the graft, alteration in blood pressure control, reduction of urine output, Doppler US evidence of subcapsular hematoma, and elevated resistive indices, as pathognomonic of this phenomenon [ 3 ]. This case report of Page kidney in a patient with acute cell-mediated rejection and no other risk factors or medications for postprocedural bleeding [ 8 ], presenting with minimal symptoms and significant decline in renal transplant function, highlights the need for vigilance in the postbiopsy period to ensure graft viability. A similar case of Page kidney in a patient with acute humoral rejection, reported by Chung et al in 2008, resulted in the patient becoming dialysis-dependent despite surgical decompression [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, a sixfold increase in major complications seen in patients who had taken 325 mg of aspirin within 3 days of biopsy (OR, 6.3; 95% CI, 1.27-31.3). 26 Mackinnon et al also suggested no difference in major complication rate with aspirin continuation. 27 Pieper et al examined the effects of recent clopidogrel use in 69 patients on major complications after percutaneous core biopsy, with a mean time of clopidogrel abstinence before biopsy being 2.9 days AE 1.9 days and found no major complications after PRB.…”
Section: Thrombocytopenia and Platelet Dysfunctionmentioning
confidence: 96%